Characterization Of Sedimentary Process In An Estuarine Environment Based On Grain Size Trend Analysis And Geochemical Trace Element In The West Flood Canal River, Semarang. Issue 1 (1st July 2022) - Devienna, S N; Nugroho, S H; Kurniasih, A; Putra, P S; Lestari,; Awibowo, S P; Kaisupy, M T; Amar,; Jakah,
Abstract: The West Flood Canal River is one of the major rivers that flows the central of Semarang Bay. The west flood canal river is located in the middle of a densely populated residential and used as city drainage in the Semarang. Unfortunately, the upper part of the river has been swallowed up. This river has unique sedimentation dynamics, so it becomes a suitable research object to determine the relationship between river sedimentation processes and the concentration of trace elements contained in the sediment. A core sample was taken at the mouth of the west canal flood river for research purposes. The analysis included grain-size trend analysis (GSTA) and geochemical trace elements on 40 sub-samples of sediment core slices within 1 cm intervals. Afterward, the GSTA results were grouped by clustering to obtain lithofacies. Each lithofacies has geochemical characteristics that indicate changes in environmental conditions over a period of time. The GSTA showed that the sediment core is dominated by coarse silt to fine silt. The cluster showed there are at least 5 lithofacies, which have different sedimentary characteristics. In general, the character of the sediment which is dominated by coarser grain size has a higher concentration of Fe, Ca, Mn, Ti, and lower levels of K. On the other hand, the sediment group which has a sedimentary character dominated by fine grain size has a lower content of Fe, Ca, Mn, Ti, and higher K levels.